Quantitative perfusion analysis in pancreatic contrast enhanced ultrasound (DCE-US): a promising tool for the differentiation between autoimmune pancreatitis and pancreatic cancer - Vitali, F.; Pfeifer, L.; Janson, C.; Goertz, R. S.; Neurath, M. F.; Strobel, D.; Wildner, D. (Zeitschrift für Gastroenterologie, 2015)
In the work-up of focal pancreatic lesions autoimmune pancreatitis (AIP) is a rare differential diagnosis to pancreatic cancer (PC) with similar clinical constellations. The aim of our study was to compare differences between proven AIP and PC using transabdominal dynamic contrast enhanced ultrasound (DCE-US). Therefore we recorded 3-minute-clips of CEUS examinations and analyzed perfusion parameters with VueBox®-quantification software. To obtain DCE-US Parameters, Regions-of-Interest were selected within the lesions and the surrounding pancreas parenchyma, serving as reference tissue. We compared 3 patients with AIP (mean age: 58 years; lesion mean size: 40 mm) to 17 patients with PC (mean age: 68 years; lesion mean size: 35.9 mm). Significant differences between PC and parenchyma could be found in the following parameters: Peak-Enhancement (PE), Wash-in-and-Wash-out-AUC, Wash-in Perfusion-Index. PE of AIP was comparable to normal parenchyma. The relation of PE between parenchyma and lesion (ΔPE) AIP and PC was significantly different [AIP: 0.21 (± 0.06); PC: 0.81 (± 0.1); p < 0.01]. PE of neoplastic lesions was significantly lower as AIP and normal parenchyma (p < 0.01). Therefore perfusion analysis in DCE-US can help to differentiate hypovascular PC from AIP presenting nearly isovascular time intensity curves. Diagnostic accuracy of DCE-US in this setting has to be validated in future prospective studies in comparison to CT and MRI.
Keywords: Kontrastmittelsonografie; Pankreaskarzinom; Autoimmunpankreatitis; quantifizierende Perfusionsanalyse